AB0621 Development of systemic sclerosis in transgendered females: a case series. (15th June 2017) - Campochiaro, C; Fonseca, C; Derrett-Smith, E; Ong, VH; Denton, CP
Abstract : Background: Scleroderma (SSc) is an autoimmune connective tissue disease with a female preponderance (female to male ratio of 9.7:1) [1]. Sex hormones are thought to play a role in the susceptibility to autoimmune diseases [2]. Objectives: We report 3 cases of SSc in male-to-female transsexuals diagnosed following their male-to-female transition Methods: Medical records of 3 patients diagnosed with SSc after male-to-female transition were reviewed. Disease features, hormonal therapies and surgical interventions related to gender reassignment were collected. Results: At our tertiary University Hospital clinical service, 3 male-to-female transsexual patients were diagnosed with SSc following their surgery between May 1997 and October 2016. All 3 patients had started their transition before the onset of the disease and had not been diagnosed with any autoimmune disease before either starting the hormonal therapy required for the transition or before undergoing plastic surgery interventions. The first case was diagnosed with anti-RNA pol III +ve diffuse cutaneous SSc at the age of 35 yearsa year after the first surgical intervention for infected silicone buttock implants and approximately 5 years of hormonal therapy with combination of mestranol and norethisterone (Norinyl-1®). She experienced scleroderma renal crisis 2 years after the diagnosis and severe vascular involvement with frequent and severe digital ulcers (DU), Raynaud's phenomenon (RP), gastroesophageal reflux disease (GERD), pulmonary arterial hypertension and telangiectasiae. She required chronic dialysis and was treated with mycophenolate mofetil (MMF), rapamycin, bosentan and proton-pump inhibitors (PPI). She eventually died 8 years after the diagnosis. The second case was diagnosed at the of 49 years, approximately 6 months following her gender reassignmentand 5 years after having started hormonal therapy initially with conjugated estrogen isolated from pregnant mares (Premarin®) and later with ethinylestradiol and gestodene (Femodene®). She developed ANA –ve, antiCCP antibody and rheumatoid factor positive limited cutaneous SSc/rheumatoid arthritis overlap syndrome and experienced severe DUs, RP, GERD, inflammatory arthritis and pulmonary fibrosis (PF). She was treated with MMF, PPI, calcium-channel blocker (CCB) and low-dose steroid therapy with good response. The third case was diagnosed at the age of 43 years, 2 years after having started triptorelin (Decapeptyl®) and oestradiol valerate. She had not undergone any surgical intervention prior to her diagnosis. She developed anti-PM/Scl +ve limited cutaneous SSc/myositis overlap syndrome and experienced RP, GERD and PF. She has only been treated with PPI and CCB prior to her reconstructive surgery. Conclusions: Although still debated, the role of sex hormones in triggering autoimmunity has been suggested in animal models and human studies [2]. The development of SSc in our case series supports the notion that altered profile of sex hormones may modulate autoimmunity in genetically susceptible individuals with distinct clinical and laboratory characteristics. References: Barnes J et al. Epidemiology of systemic sclerosis: incidence, prevalence, survival, risk factors, malignancy, and environmental triggers. Curr Opin Rheumatol 2012. Pennell LM et al. Sex affects immunity. J autoimmun 2012. Disclosure of Interest: None declared